2004
DOI: 10.1590/s1415-47572004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by RAPD of the genetic structure of Astyanax altiparanae (Pisces, Characiformes) in reservoirs on the Paranapanema River, Brazil

Abstract: In this study, the RAPD technique was used to analyze the genetic structure of populations of the fish Astyanax altiparanae (Characidae, Tetragonopterinae) living in the lower, middle and upper Paranapanema River, Brazil. The aim was to assess this structure regarding fish handling and conservation programs. The genetic variability (P) was found to be 42.64%, 75% and 75% in the low, middle and upper reaches, respectively. The dendrogram of genetic similarity, obtained by comparative analysis of the sets of sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 20 publications
(27 reference statements)
3
33
0
13
Order By: Relevance
“…The highestP and H E values were observed in A. altiparanae and the lowest values in L. amblyrhynchus (Table 2). All levels of genetic diversity in the populations studied here were evaluated as satisfactory compared to previously reported data (Chiari and Sodré, 2001;Almeida et al, 2003;Leuzzi et al, 2004;Pamponet et al, 2008). …”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The highestP and H E values were observed in A. altiparanae and the lowest values in L. amblyrhynchus (Table 2). All levels of genetic diversity in the populations studied here were evaluated as satisfactory compared to previously reported data (Chiari and Sodré, 2001;Almeida et al, 2003;Leuzzi et al, 2004;Pamponet et al, 2008). …”
Section: Discussionmentioning
confidence: 60%
“…Other studies found genetic distance values higher than here and considered these values to indicate low levels of genetic differentiation. Populations of Astyanax altiparanae studied by Leuzzi et al (2004) gave genetic distance estimates close to 0.12 in an area without geographical barriers; Sofia et al (2006) found higher levels of genetic distance (approximately 0.61) for Astyanax scabripinnis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Many molecular markers have been frequently used for the Astyanax species (Prioli et al 2002;Leuzzi et al 2004;Peres et al 2005). However, there are no microsatellite data available for this group.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, very limited information on fish populations in Lake Laut Tawar is available. In many situations, genetic data are the best way to determine whether a species is worth a special protection under the Endangered Species Act (ESA) or other form of conservation status (Matoso et al 2004), as it allows calculated decisions on the best course of action to be taken for protection and conservation (Leuzzi et al 2004) as well as managing different stocks (Salini et al 2006).…”
mentioning
confidence: 99%